Digitalization of OHS Management Process in Road Construction Projects with User-Centered Design Approach - Salma, Sheila Amalia; Marliana, Wina (International Journal of Innovation in Enterprise System, 2025)
In Indonesia, workplace innovation in the context of Occupational Health and Safety (OHS) has great potential to shape the future of a safer and healthier workplace. One of the innovations in the workplace is the digitalization of the OHS management process. The proposed digitalization of the OHS management process is used as a system that documents and reports in an integrated and real-time manner related to the OHS management process in road construction. The need for a system that does not make workers overload information is very necessary and the system design must also be adjusted to user needs. The purpose of this study is to design the digitalization of the OHS management process in road construction projects with a User-Centered Design approach. Observation, interviews, and focus group discussions are used as data collection methods. The UCD is a design approach that focuses on user needs as the center of design. The stages are identification of user context, specification of user needs, solution design, and evaluation. The results obtained are that the designed digitalization has helped companies in controlling the risk of work accidents and helping companies in implementing a better OHS management system. In addition, the result of this research is a system design that documents and reports in an integrated and real-time way related to OHS management with a user approach, so that the issue of over-information can be minimized.